Realizing Family Resilience during the Covid-19 Pandemic through Health Education and Counseling for Aisyiyah Cadre in Sewon District, Bantul - Dody Hartanto; Ratu Matahari; Desi Nurfita (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2022)
Domestic Violence (KDRT) is on the rise during the COVID-19 pandemic. According to data from the Ministry of PPPA, there are an average of three cases of violence against adult women (>=18 years) per day. Domestic violence experienced by women reached 114 victims during the pandemic era, which was caused by most people losing their jobs and the economy declining. It contributes to the deterioration of family resilience. This Community Service is intended to educate and train Aisyiyah cadres. This activity employs a health education and counseling method to foster family resilience. This community service activity helps participants understand pre- and post-test results. Community service activities have a positive impact on the family's knowledge and problem-solving skills. The role of Aisyiyah cadres in reducing domestic violence during the Covid-19 pandemic is significant